DESCRIPTION OF URIC ACID LEVELS PRE AND POST WARM COMPRESS OF MORINGA LEAF (Moringa oleifera Lam) IN PATIENTS WITH JOINT PAIN IN ULOK KUPAI DISTRICT, BENGKULU UTARA DISTRICT, 2023 - Delta Nosi Wulandari; Putri Widelia Welkriana; Halimah Halimah (Poltekkes Kemenkes Bengkulu, 2023)
Uric acid is the final metabolic product of purines, which is a component of nucleic acids found in the nucleus of body cells. Moringa plant (Moringa oleif-era) is a local food ingredient that has the potential to cure gout naturally, because Moringa leaves contain active compounds, namely flavonoids and alkoloids which can prevent the formation of uric acid, besides that Moringa leaves can also be used as an anti-inflammatory. inflammatory (inflammation) and analgesic (pain relief). The purpose of this study was to find out the levels of uric acid before and after warm compresses of Moringa leaves in sufferers of joint pain in the Ulok Kupai sub-district, North Bengkulu Regency in 2023. The type of research conducted was descriptive research with a quasi-experimental design, namely describing and describing the effects before and after applying warm compresses to Moringa leaves to see differences in uric acid levels. From the results of a study conducted on 20 respondents, it was found that the average uric acid level before applying warm compresses was 7.89 and after applying warm compresses it was 7.22. The results of the pain scale were also obtained, namely, moderate pain before applying warm compresses for 1 person (5%), after applying warm compresses it became mild pain. Severe pain before applying warm compresses as many as 13 people (65%), after applying warm compresses to moderate pain. Unbearable pain in 6 people (30%) after applying warm compresses became severe pain. From the variable uric acid levels, the average value of uric acid levels before warm compresses is 7.89 and after warm compresses is 7.22. It can be seen that 100% of respondents experienced joint pain with pain levels divided into 4 levels. Moderate pain before applying warm compresses in 1 person (5%), after applying warm compresses becomes mild pain. Severe pain before applying warm compresses as many as 13 people (65%), after applying warm compresses to moderate pain. Unbearable pain in 6 people (30%) after applying warm compresses became severe pain. It is hoped that it can provide information and the alternate to use this moringa to the public regarding the benefits of using Moringa leaves as a lowering of uric acid levels in sufferers of joint pain.